Eyelid skin trichilemmoma and underlying local malignancy: is an aggressive treatment necessary?. Issue 1 (25th June 2020) - Putri, Christine Anggun; Mudhar, Hardeep Singh; Meeney, Adam; Tan, Jennifer H Y
Abstract : Objective: Trichilemmoma is a benign tumour derived from the outer root sheath of hair follicles. Trichilemmoma can be associated with basal cell carcinoma (BCC), either as a collision lesion or from malignant transformation. This study evaluates malignancy associated with eyelid trichilemmoma and principles of treatment. Methods and analysis: Retrospective study involving biopsy-proven eyelid trichilemmoma cases over 14 years encountered at a tertiary referral centre. Presenting features, differential diagnosis, type and number of operations required and histopathological features including coexisting BCC were analysed. Results: We identified 36 cases with an average age of 66 years. The clinical differential diagnoses were mainly BCC (44%), papilloma (36%) and squamous cell carcinoma (SCC) (3%). Three patients (8%) had trichilemmoma with associated BCC. Of the 19 cases (53%) of trichilemmomas without BCC with equivocal surgical margins, seven patients (19%) opted for further excision while 12 patients (33%) opted for observation and were discharged. A patient re-presented two years later with invasive BCC. Overall, 11% of our biopsy-proven eyelid trichilemmoma cases were associated with BCC. Conclusion: Patients should be informed that a proportion of incompletely excised eyelid trichilemmomas may conceal underlying BCC. Therefore, further surgery to achieve clear surgical margins should be offered. Patients who opt for observation should be offered 6-monthly follow-up for three to five years. Alternatively, they can be discharged with advice to report any recurrence of lumps, skin changes or loss of lashes at the site of previous lesion.